Exploring Feminist Concerns In A Cultural Context: The Voices Of Service Providers For Sex Trafficked Females In Jordan - Samoudi, Nora; Larsen, Ann-Claire (2016)
In this paper, I discuss feminist discourse in relation to the cultural context of sex-trafficking crimes in Jordan. I reveal evidence in the paper that the patriarchal code of honour in Jordan intimidates sex trafficked females, preventing them from exiting their underground sex-work and returning to their families. The diverse cultural groups in Jordan, which include indigenous Jordanians, Bedouins, Gypsies, Syrian refugees, Iraqi refugees and other minority groups, have created layers of vulnerability for women and girls that contribute to them becoming victims of sexual exploitation. To describe females’ vulnerability to several norms and complexities, I draw on my ethnographic study, which was conducted in Amman, Jordan in 2015-16. I interviewed seven service providers who work for organisations providing services for rescued female victims of sex trafficking. They provide refuge for domestic and nondomestic victims of sex trafficking. In addition, I observed aspects of Jordanian culture, enabling me to describe the changing social and cultural situation affecting trafficked women. This paper argues for adopting an approach that accounts for the categories of vulnerability for understanding women’s inequalities, and informing legal reforms for improving the situation for sex trafficked victims.